Innovations and Tools in Child Growth Measurement and Data Visualization - World Bank Group (World Bank, Washington, DC, 2019)
Despite global efforts to address malnutrition, the numbers of children under five who are not growing properly are alarming: 150.8 million (22.2 percent) are stunted (too short for their age), 50.5 million (7.5 percent) are wasted (too thin for their height), and 38.3 million (5.6 percent) are overweight (too heavy for their height). Children living in lower-middle income countries (LMIC) are particularly affected. At these rates, the world is off course to reach the World Health Assembly targets for 2025 and the Sustainable Development Goals for 2030.